Strategi Public Relations Di Era Digital Di Tengah Berkembangan AI - Denda Nova Adriantini; Tekla Rensiana Toyo; Tina Tunnisa; Nahsanil Fitri; Widia Kharisma; Rosmini; Muhammad Rahmatul Burhan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The rapid development of digital technology has changed the landscape of public relations (PR), encouraging organizations to adapt quickly in the way they communicate and build relationships with the public. This research aims to understand and develop relevant and effective PR strategies in the digital era, where the use of new media is the key to reaching audiences in a fast and efficient way. With a qualitative approach through literature study, analysis was carried out on various sources covering the positive and negative impacts of technology, including the use of artificial intelligence (AI) in PR. The results show that although AI offers efficiency and deep data analysis, there are risks of technology dependency and privacy concerns. This research emphasizes the importance of new skills for PR practitioners to be able to face modern challenges, while serving as a bridge between organizations and society. With an innovative approach, PR can improve brand reputation and awareness, and build stronger relationships in this digital era